2022
DOI: 10.1016/j.asmr.2021.11.015
|View full text |Cite
|
Sign up to set email alerts
|

The Addition of Suture Tape to the Hamstring Graft Construct Does Not Reduce Instrumented Knee Laxity Following ACL Reconstruction

Abstract: Purpose: To establish the effect of the addition of suture tape to the hamstring graft construct through measurement of instrumented sagittal plane knee laxity at 6 months after anterior cruciate ligament reconstruction (ACLR). Methods: A retrospective analysis was undertaken of a consecutive series of primary ACLR performed between May 2017 and June 2019. Patients with concomitant or historic contralateral knee injury were excluded. Suture tape was included in the graft construct from the midpoint of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 15 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…Critical application of the inclusion and exclusion criteria finally yielded nine studies ( Figure 2 ). One was a prospective cohort study (level 2) ( Shantanu et al, 2019 ), six were retrospective cohort studies (level 3) ( Bodendorfer et al, 2019 ; Parkes et al, 2021 ; Allom et al, 2022 ; Kitchen et al, 2022 ; Szakiel et al, 2022 ; von Essen et al, 2022 ), and two were case series (level 4) ( Lavender et al, 2021 ; Duong et al, 2022 ). All seven comparative studies were designed to compare patients who underwent ACLR with and without ST-augmented grafts ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Critical application of the inclusion and exclusion criteria finally yielded nine studies ( Figure 2 ). One was a prospective cohort study (level 2) ( Shantanu et al, 2019 ), six were retrospective cohort studies (level 3) ( Bodendorfer et al, 2019 ; Parkes et al, 2021 ; Allom et al, 2022 ; Kitchen et al, 2022 ; Szakiel et al, 2022 ; von Essen et al, 2022 ), and two were case series (level 4) ( Lavender et al, 2021 ; Duong et al, 2022 ). All seven comparative studies were designed to compare patients who underwent ACLR with and without ST-augmented grafts ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…For all studies, the use of ST was based on the surgeon’s preference, except for one prospective cohort study with randomized selection. Concomitant lateral extra-articular tenodesis was performed in one study ( Allom et al, 2022 ) for 84/169 patients with risk factors for graft rupture.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Much of the research focuses on determining the best graft choice for these patients. Previous studies reported that suture tape augmentation of ACLR increases biomechanical stability and reduces complications [1, 8, 25]. Although the benefits of this solution are theoretically appealing, its clinical advantages still need to be clarified.…”
Section: Introductionmentioning
confidence: 99%